IMPLEMENTASI PEMBERIAN KERINGANAN POKOK PAJAK KENDARAAN BERMOTOR DAN PEMBEBASAN POKOK BEA BALIK NAMA KENDARAAN BERMOTOR KEDUA DAN SETERUSNYA YANG BERASAL DARI LUAR PROVINSI KALIMANTAN TIMUR DI SAMARINDA - Lia Fitri Muslim (Jurnal Administrative Reform, 2017)
The purpose of this study to describe and analyze the implementation of Provision of Basic Motor Vehicle Tax Relief And Principal Customs Exemption of Vehicle Second and Beyond Derived From Outer East Kalimantan Province in Samarinda. The results showed that the policy of granting waivers principal motor vehicle tax (PKB) and the transfer tax exemption of motor vehicles (BBNKB) Second and Beyond Originating from Outside the Province of East Kalimantan in Samarinda (PKB and BBNKB) are implementable less than optimal. Indicated by sub focus of research defined, not everything can be implemented effectively.